Computing Statistical Precision of Efficiency and Productivity Change Indices: A Bootstrap Application to Ghanaian Polytechnics - Mends-Brew, Edwin; Ashiagbor, Albert Ayi (European Scientific Journal, ESJ, 2016)
This study employs a bivariate smoothing bootstrap technique to obtain a statistical inference for Technical Efficiency and Malmquist Indices and their components of Polytechnics in Ghana over the period 2009-2014. The main contribution of this paper is to provide an Efficiency Analysis using a non-parametric approach with a robust estimator. This methodology is empirically being applied in the analysis of Polytechnic Education in Ghana because it affords us the opportunity to compute the statistical significance of changes in Polytechnics’ Technical Efficiency and Productivity Indices and their respective components. Results showed that averagely, Technical Efficiency fluctuated over the period; however, Polytechnic Education experienced a significant technological regress, with few Polytechnics achieving increases in productivity led by improvements in efficiency. Policy implications are derived.